Association of interceptive orthodontic treatment need and pediatric sleep-related breathing disorder: Study cross-sectional - Sasmita, Josephine; Yusra, Yohana; Marpaung, Carolina Damayanti (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRACTIntroduction: Early childhood malocclusion refers to the misalignment of teeth during the mixed dentition phase in children, which can affect breathing during sleep. One intervention for early childhood malocclusion is interceptive orthodontic treatment. This study aims to determine the relationship between the need for interceptive orthodontic treatment and Sleep-Related Breathing Disorders (SRBD) in children aged 8-11 years. Methods: This research is an analytic observational study with a cross-sectional design. The sample includes parents and their children aged 8-11 years (mixed dentition phase) who are attending Bukit Sion Elementary School. Inclusion criteria include parents with children aged 8-11 years in the mixed dentition phase at Bukit Sion Elementary School who are physically healthy. Exclusion criteria include children currently undergoing or having previously undergone orthodontic treatment and those who did not complete all required forms. Intraoral examinations were conducted on the children by dentists using the Indeks Kebutuhan Perawatan Ortodonti Interseptif (IKPO-I) form, while parents completed the Pediatric Sleep Questionnaire (PSQ). Results: A total of 76 students from Bukit Sion Elementary School, West Jakarta, participated in the study. The results of the examination using IKPO-I indicated that 47 children (61.8%) required interceptive orthodontic treatment. The results of the PSQ questionnaire revealed that 7 children (9.2%) were at high risk for SRBD. Statistical analysis with the Spearman correlation test showed no significant relationship between interceptive orthodontic treatment need and SRBD risk (p = 0.087; rs = 0.198). Conclusions: There is no correlation between interceptive orthodontic treatment need and pediatric SRBD in children aged 8-11 years. Further research employing more reliable measurement methods and tools is necessary to provide a clearer understanding of the relationship.KEY WORDS: Malocclusion, interceptive orthodontics, IKPO-I, mixed dentition, sleep-related breathing disorderKorelasi kebutuhan perawatan ortodonti interseptif dan Sleep-Related Breathing Disorder pada anak: Studi cross-sectionalABSTRAKPendahuluan: Maloklusi pada anak usia dini (early childhood malocclusion) adalah ketidaksejajaran gigi dalam periode gigi bercampur yang dapat memengaruhi pernapasan saat tidur. Penelitian ini bertujuan untuk menganalisis korelasi antara kebutuhan perawatan ortodonti interseptif sebagai intervensi dini maloklusi, dan Sleep-Related Breathing Disorder (SRBD) pada anak usia 8-11 tahun. Metode: Jenis penelitian merupakan observasional analitik dengan desain potong lintang. Sampel dalam penelitian ini adalah orang tua dan anaknya yang berumur 8 – 11 tahun (periode gigi bercampur) dan bersekolah di SD Bukit Sion, Jakarta Barat. Kriteria inklusi dalam penelitian ini mencakup orang tua dan anaknya yang berusia 8-11 tahun dalam periode gigi bercampur di SD Bukit Sion, dan sehat secara fisik. Kriteria eksklusi mencakup subjek yang sedang atau pernah menjalani perawatan ortodonti serta yang tidak melengkapi seluruh formulir yang diperlukan. Pemeriksaan intra oral pada anak dilakukan oleh dokter gigi menggunakan formulir Indeks Kebutuhan Perawatan Ortodonti Interseptif (IKPO-I) dan pengisian Pediatric Sleep Questionnaire (PSQ) dilakukan oleh orang tua. Hasil: Subjek penelitian diperoleh sebanyak 76 murid SD Bukit Sion. Hasil pemeriksaan menggunakan IKPO-I diperoleh sebanyak 47 anak (61,8%) membutuhkan perawatan ortodonti interseptif. Hasil kuesioner PSQ diperoleh 7 anak (9,2%) berisiko tinggi memiliki SRBD. Analisis statistik dengan uji korelasi Spearman menunjukkan tidak terdapat korelasi yang signifikan antara kebutuhan perawatan ortodonti interseptif dan risiko SRBD (p = 0,087; rs = 0,198). Simpulan: Tidak terdapat korelasi antara kebutuhan perawatan ortodonti interseptif dan SRBD pada anak usia 8-11 tahun. Studi lanjut dengan metode dan alat pengukuran yang lebih akurat diperlukan untuk mengklarifikasi hubungan ini.KATA KUNCI: Maloklusi, ortodonti interseptif, IKPO-I, periode gigi bercampur, sleep-related breathing disorder